Hubungan antara Kualitas Komunikasi Keluarga dan Persepsi tentang Abusive Relationship dengan Perilaku Kekerasan dalam Pacaran Kelompok Usia Dewasa Muda - Astari, Cynthia; Pudjo Santosa, Hedi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Family communication that takes place with violence will form individuals with similarbehavior. In addition, one's behavior is also supported by how he perceives everything, includingregarding abusive relationships. Therefore, this study aims to determine the correlations betweenthe quality of family communication and perceptions of abusive relationship with young adultsabusive dating behavior. The study was conducted with a nonprobability sampling technique,namely purposive sampling in the age group of 18 to 30 years who were/had undergone aromantic relationship (dating), and had experience in dating violence. The number of samples inthis study were 60 people with a ratio of 50 percent of women and 50 percent of men so that thestudy was balanced.Based on the hypothesis analysis of the Kendall’s Tau b correlation analysis shows a negativecorrelation between the quality of family communication with young adults abusive datingbehavior with its significance value of 0,000 (<0.05) and the correlation coefficient of 0.334. Thecorrelation between the quality of family communication with young adults abusive datingbehavior can be explained through social cognitive theory, that humans have the ability toindependently observe the surroundings which then influence the behavior imitation decisionsthat they see. This means that the higher the quality of family communication that takes place,the lower a person's abusive behavior in dating. Furthermore, there is a positive correlationbetween perceptions of abusive relationship with young adults abusive dating behavior with itssignificance value of 0.005 (<0.05) and the correlation coefficient of 0.239. The relationship ofthese two variables can be explained through social judgement theory (acceptance and rejectionapproach), how one's perceptions of abusive relationships are tailored to individual interests intheir social relationships which then influence the way they behave. This means that the better aperson's perception of abusive relationship, the higher the abusive behavior carried out. Thus, theauthor suggests by improving the quality of family communication and dropping bad perceptionsof abusive relationships can avoid the risk of abusive dating behavior.